2018
DOI: 10.3390/publications6040047
|View full text |Cite
|
Sign up to set email alerts
|

Journals that Rise from the Fourth Quartile to the First Quartile in Six Years or Less: Mechanisms of Change and the Role of Journal Self-Citations

Abstract: Journal self-citations may be increased artificially to inflate a journal’s scientometric indicators. The aim of this study was to identify possible mechanisms of change in a cohort of journals that rose from the fourth (Q4) to the first quartile (Q1) over six years or less in Journal Citation Reports (JCR), and the role of journal self-citations in these changes. A total of 51 different journals sampled from all JCR Science Citation Index (SCI) subject categories improved their rank position from Q4 in 2009 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 53 publications
0
4
0
1
Order By: Relevance
“…There is no unanimity regarding excluding self-citations in impact indicators (Campanario, 2018;Huang;Cathy Lin, 2012). There is a consensus that at the micro (author, journal) and meso (institution) levels, the influence of self-citation on the impact analysis is significant (Yu;Yu;Wang, 2014), and exclusion may be necessary.…”
Section: Journal Self-citationmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no unanimity regarding excluding self-citations in impact indicators (Campanario, 2018;Huang;Cathy Lin, 2012). There is a consensus that at the micro (author, journal) and meso (institution) levels, the influence of self-citation on the impact analysis is significant (Yu;Yu;Wang, 2014), and exclusion may be necessary.…”
Section: Journal Self-citationmentioning
confidence: 99%
“…Journal self-citation has received significant attention recently (Chorus;Waltman, 2016;Gazni;Didegah, 2021;Heneberg, 2016;Taşkin et al, 2021;Wilhite;Fong, 2012). This interest may have originated from the perception that self-citations, and not the growth of impact, may be the main reason for the increase in indicators of some journals (Campanario, 2018;Heneberg, 2016). This alerted the need to identify self-citation patterns in databases and analyze journals with excessive self-citation rates (Gazni;Didegah, 2021;Taşkin et al, 2021;Yu;Yu;Wang, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…asegurar una ubicación real. Así mismo, Campanario (2018) al estudiar las razones por las cuales algunas revistas han logrado mejorar su posición en los cuartiles en un lapso corto de tiempo (6 años) concluye que se debe principalmente a que solo se toma en cuenta el Factor de Impacto, el cual logran aumentar disminuyendo el número de documentos publicados, lo que hace que aunque bajen las citas, el indicador se mantiene o aumenta, una estrategia que pareciera encaminada a que las revistas publiquen menos artículos pero de mayor calidad, sin embargo no está del todo comprobado. Por su parte, Asan y Aslan (2020) consideran que, aunque la ubicación de las revistas científicas en cuartiles proporciona información valiosa en términos de citación y clasificación en sus categorías científicas, a los efectos de los nombramientos de personal académico puede ser malinterpretado, por lo que su uso debe hacerse con la cautela debida.…”
Section: Cuartil Actualunclassified
“…Campanario indicated the way self-citations of 51 selected journals from the JCR-SCI field affect the journal's impact factor and Q scores [11]. Tayyab and Boyce reported that the impact factor scores of 39 journals selected from different scientific disciplines in the Q1 category ranged from 0.611-1.979 (below 2), whereas the journals in the biochemistry-molecular biology category were at least 4.405 and above [12].…”
Section: Meaning and Usage Of Quartile Scores Of Scientific Journalsmentioning
confidence: 99%